Research of marketing potential of Ukrainian startup project - Shcherbik, Olena (2020)
The main purpose of this work is to research of marketing potential of Ukrainian social startup project public restaurant «Urban Space» to choose and justify a marketing potential evaluation model that will have further application as well as setting recommendations based on it. The data was collected from official website «Urban Space» and from experts evaluation of marketing potential. To determine the marketing potential were chosen Batova and Krilova (2016) model. The level of the marketing potential of «Urban Space» within a general goal in 2017 was low (0.59). By 2018, was reached an average level of marketing potential (0.85). Based on the evaluation results of marketing potential within a specific goal, for implementation goal «increase of market share» the level of marketing potential is low (0.58), for implementation goal «customer retention» is an average level of marketing potential (0.63). Therefore, was recommend a number of factors for actively contributing of customer retention.